Psicopatia: uma proposta de regime especial para cumprimento de pena - Savazzoni, Simone de Alcantara (2017)
Psycopathy is a subject that challenges for a long time, criminal science and justice itself. In order to exemplify some points on such theme, in this thesis, it Will be performed an analytical descriptive study aiming in specially, analyze by which means psycopathy introduces itself to medicine, psychology, aiming in explore interdisciplinary on the legal aspect and penal processing criminal law. The starting point to differ will be: psycopathy from the mental disease concept in order to frame it as a personality disorder, with the objective of appraising liabilities on the psychopath individual with aims of applying responsibility upon crime committed. It will also be demonstrated, how does punishment measures adopted, currently, take place upon criminal psychopaths – measures of security of prison penalty – reflect and impact such individual, which is differed from the others due to a lack of sorrow and non capability of learning upon punishments received after it. The proposal is to reflect on the presence of such subject in the Brazilian prison system, especially, by taking into account indicative studies on higher reoccurrence fee. It will be presented, nevertheless, a critical view on the current assessments of behavior as a requisite subject to approval on benefits during penalty execution – looking forward to evaluate the State – whether they present physical structure and qualified workforce to deal with accomplishment of penalty by the psychopath, highlighting lacks in the current system. It will also be verified on the Brazilian legislation mismatch with discoveries required by medical and psychological sciences about psychopathy. Finally, demonstrated current imperfection on the prison system on the application and accomplishment of penalty by the psychopath, this thesis will propose a special regime to these subjects, which will be implemented as an adequate establishment and effective follow up with multidisciplinary team duly qualified